Exploring Tourism Potential in Bajhang District of Nepal: A Case Study (Nepalese Journal of Hospitality and Tourism Management, 2025)
Bajhang district, located in Nepal’s far-western Sudurpaschim Province, is a region of immense yet underutilized tourism potential, characterised by its rugged landscapes, sacred sites, and rich cultural heritage. This qualitative study explores Bajhang’skey attractions, including the Saipal Himal, Surma Sarovar Lake, Khaptad National Park, and historic temples—while identifying critical challenges hindering tourism development. Through interviews with local stakeholders, including bankers, hoteliers, social workers, and business owners, the research highlights persistent issues such as poor infrastructure, unclear government policies, corruption, low public awareness, and insufficient funding. Despite these barriers, Bajhang holds significant opportunities for adventure, religious, and eco-tourism, provided there is coordinated investment in road connectivity, sustainable lodging, and community-based tourism initiatives. The study recommends policy reforms, infrastructure upgrades, targeted marketing, and stronger public-private collaboration to position Bajhang as a competitive tourism destination. By addressing these challenges, Bajhang can leverage its natural and cultural assets to stimulate local economic growth, reduce migration, and establish itself as a key tourism hub in western Nepal.